The Hispanic Paradox in Patients With Liver Cirrhosis: Current Evidence From a Large Regional Retrospective Cohort Study. Issue 12 (December 2019) - Atiemo, Kofi; Mazumder, Nikhilesh R.; Caicedo, Juan C.; Ganger, Daniel; Gordon, Elisa; Montag, Samantha; Maddur, Haripriya; VanWagner, Lisa B.; Goel, Satyender; Kho, Abel; Abecassis, Michael; Zhao, Lihui; et al.
Abstract : Background: Despite lower socioeconomic status, Hispanics in the United States paradoxically maintain equal or higher average survival rates compared to non-Hispanic Whites (NHW). Methods: We used multivariable Cox regression to assess whether this "Hispanic paradox" applies to patients with liver cirrhosis using a retrospective cohort of twenty 121 patients in a Chicago-wide electronic health record database. Results: Our study population included 3279 (16%) Hispanics, 9150 (45%) NHW, 4432 (22%) African Americans, 529 (3%) Asians, and 2731 (14%) of other races/ethnic groups. Compared to Hispanics, NHW (hazard ratio [HR] 1.26; 95% confidence interval [CI], 1.16-1.37), African American (HR 1.26; 95% CI, 1.15-1.39), and other races/ethnic groups (HR 1.55; 95% CI, 1.40-1.71) had an increased risk of death despite adjustment for age, sex, insurance status, etiology of cirrhosis, and comorbidities. On stratified analyses, a mortality advantage for Hispanics compared to NHW was seen for alcohol cirrhosis (HR for NHW 1.35; 95% CI, 1.19-1.52), hepatitis B (HR for NHW 1.35; 95% CI, 0.98-1.87), hepatitis C (HR for NHW 1.21; 95% CI, 1.06-1.38), and nonalcoholic steatohepatitis (HR for NHW 1.14; 95% CI, 0.94-1.39). There was no advantage associated with Hispanic race over NHW in cases of hepatocellular carcinoma or cholestatic liver disease. Conclusions: Hispanic patients with cirrhosis experience a survival advantage over many other racial groups despite adjustment for multiple covariates. Abstract : Supplemental Digital Content is available in the text.